2023
DOI: 10.1097/sle.0000000000001235
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Effect on Minimally Invasive Ventral Hernia Repair: A Systematic Review and Meta-analysis

Sergio Mazzola Poli de Figueiredo,
Rui-Min Diana Mao,
Giovanna Dela Tejera
et al.

Abstract: Purpose: Obesity is one of the most important risk factors for complications after ventral hernia repair (VHR), and minimally invasive (MIS) techniques are preferred in obese patients as they minimize wound complications. It is common practice to attempt weight loss to achieve a specific body mass index (BMI) goal; however, patients are often unable to reach it and fail to become surgical candidates. Therefore, we aim to perform a meta-analysis of studies comparing outcomes of obese and nonobese pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Patients who were underweight or overweight were not considered. The primary outcomes evaluated were surgical wound dehiscence, surgical site infection (SSI), including superficial and deep wounds, bleeding that required transfusion, deep venous thromboembolism (DVT), and postoperative abscess formation as defined by individual studies [ 14 , 15 ]. These outcomes were selected as they are the most commonly studied in different meta-analyses that evaluate the effect of obesity on surgical outcomes within the adult population.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who were underweight or overweight were not considered. The primary outcomes evaluated were surgical wound dehiscence, surgical site infection (SSI), including superficial and deep wounds, bleeding that required transfusion, deep venous thromboembolism (DVT), and postoperative abscess formation as defined by individual studies [ 14 , 15 ]. These outcomes were selected as they are the most commonly studied in different meta-analyses that evaluate the effect of obesity on surgical outcomes within the adult population.…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, Liu et al reported that BMI ≥30 kg/m 2 resulted in significantly higher SSI after colorectal surgery [ 42 ]. However, some other studies in adult populations have found no difference based on BMI for SSI, such as in the case of inguinal hernia repair [ 14 ]. In our study, encompassing different types of surgery, we found that obese pediatric patients had a 1.63 times higher risk of developing an SSI compared to normal-weight patients.…”
Section: Reviewmentioning
confidence: 99%